2017
DOI: 10.5267/j.esm.2017.2.001
|View full text |Cite
|
Sign up to set email alerts
|

Friction stir welding process: An investigation of microstructure and mechanical properties of Al Alloy AlMg4.5Mn joint

Abstract: Aluminium alloy AlMg4.5Mn has got comprehensive acceptance in the manufacturing of light weight frames, marine structures which require high strength and worthy corrosion revulsion. The present investigation work focuses on friction stir welding process in which influences of operating parameters have been studied on friction stir welded butt joints. The FSWed joints specimens have been produced by experimentation at three levels of tool traverse speed and tool rotational speed keeping input force and tool til… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Rao et al [19] found friction stir welding in ISO: 65032 aluminium alloy to investigate its influence on tool spindle speed and joining speed. Kundu and Sigh [20] have investigated the effect of spindle speed and feed rate of the FSW process on the microstructure of AA 5083 and its effect on the mechanical properties of the join. Venkata et al [21] have used two types of tool pins, namely cone and triangle pins, by conducting FSW against AA2019 aerospace and defense aluminium alloy.…”
Section: Introductionmentioning
confidence: 99%
“…Rao et al [19] found friction stir welding in ISO: 65032 aluminium alloy to investigate its influence on tool spindle speed and joining speed. Kundu and Sigh [20] have investigated the effect of spindle speed and feed rate of the FSW process on the microstructure of AA 5083 and its effect on the mechanical properties of the join. Venkata et al [21] have used two types of tool pins, namely cone and triangle pins, by conducting FSW against AA2019 aerospace and defense aluminium alloy.…”
Section: Introductionmentioning
confidence: 99%
“…Dealing with the FSW process, most of the previous research works are focused on linear welding of plates (such as lap, butt and T‐joint welds) for different alloys 3–15 . However, reliable and practical usage of this technique for joining cylinders, pipes and tubes requires a suitable and optimized orbital FSW on cylindrical shells.…”
Section: Introductionmentioning
confidence: 99%
“…Friction stir processing (FSP) was initially derived in 1999 from the work of (Gerlich, 2017;Mishra & Ma, 2005;Mishra et al, 2014) which took its root from a novel technique called friction stir welding (FSW) that was invented in 1991 and patented by the welding institute (TWI) of UK as a solid-state joining method. Afterwards, a large number of research papers have been published for investigating the mechanical properties, microstructure and quality of FSW and FSP components (Narasimharaju & Sankunny 2019;Kundu & Singh 2017;Jian et al 2018;Aliha et al 2016;Taheri-Behrooz et al 2018;Torabi et al 2018;Akbari et al2017Behnagh et al 2012;Shahraki et al 2013;Asadi et al 2012). Since the liberation of FSP in 1999, thousands of articles, hundreds of patents, thousands of textbooks as well as reviewed and peer-reviewed magazines had been in circulation which have been imparting life till date.…”
Section: Introductionmentioning
confidence: 99%